Immunogenicity characterization of enterotoxigenic Escherichia coli (ETEC) toxoid fusion and adhesin MEFA antigens in intradermally or intramuscularly immunized mice - Garcia, Carolina Yvette (Kansas State University, 2018)
Enterotoxigenic Escherichia coli (ETEC) strains are the most common bacterial cause of diarrhea. ETEC bacterial adherence to the small intestinal epithelial cells and delivery of enterotoxins cause diarrhea in children living in developing countries and international travelers. Currently, there are no vaccines licensed for ETEC associated children’s diarrhea and travelers’ diarrhea. Recently, toxoid fusion 3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] (toxoid fusion), adhesin MEFA (multiepitope fusion antigen) CFA/I/II/IV (CFA MEFA), and toxoid-adhesin MEFA CFA/I/II/IV-3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] (CFA-toxoid MEFA) are demonstrated to induce neutralizing antitoxin and/or anti-adhesin antibodies in intraperitoneal (IP) or subcutaneous (SC) immunized mice, suggesting these antigens are potential candidates for ETEC subunit vaccines. However, these antigens have not been examined for immunogenicity using intradermal (ID) or intramuscular (IM) routes, the routes perhaps are more suitable for human vaccine administration. In this study, toxoid fusion 3xST[subscript aN12S]-mnLT[subscript R192G/L211A], CFA/I/II/IV MEFA, alone or combined, or toxoid-adhesin MEFA CFA-3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] were ID or IM immunized to mice (8 mice per group) induced antigen-specific antibodies were titrated, and antibody neutralization activities were assessed in vitro. Data showed that mice ID or IM immunized with the toxoid fusion 3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] antigen developed anti-LT and anti-STa antibodies and mice immunized with the CFA/I/II/IV MEFA developed antibody responses to all seven adhesins (CFA/I, CS1-CS6). In addition, mice co-administered ID or IM with toxoid fusion 3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] and CFA/I/II/IV MEFA, or with toxoid-adhesin MEFA CFA-3xSTa[subscript N12S]-mnLT[subscript R192G/L211A] developed antibodies to both toxins and all seven adhesins. Antibody neutralization studies of the serum samples of the immunized mice showed that the induced antibodies neutralized enterotoxicity of LT and STa and/or inhibited adherence of ETEC or E. coli bacteria producing any of these seven adhesins. These data confirmed immunogenicity of these ETEC subunit vaccine target antigens and provide useful information for vaccine development against ETEC diarrhea.
Keywords: Diarrhea; Heat-labile toxin (LT); Heat-stable toxin (STa); Antibodies; Adhesins; EnterotoxinsEnterotoxigenic E.coli